Ancient water management and the evolution of the late Holocene wetlands. First paleoecological evidence from prehispanic raised fields of Uraba, northwestern South America (2023)
ABSTRACT: The raised fields discovered recently in the Gulf of Urabá, northwestern Colombia, extends more than 135,000 ha among the floodplains of the rivers León, Suriquí and Tumaradocito in the Chocó biogeographic region. To understand the mechanisms by which people use the wetlands under climate change of the Late Holocene, the paleoenvironmental and cultural conditions were studied using artifacts, soil micromorphology, geochemical, chronostratigraphic and palynological analyses at El Vergel archaeological site. The aim of this study is to discuss the origin of raised fields development in the León river floodplain and its relation with progressive drought, groundwater and wetland management for permanent human occupation. The results suggest that the raised fields were built around the IX century CE, during a period marked by decreased precipitation, probably related with Medieval Warm Period. The hydrogeology reveals two aquifers in the region with some shallow springs in the floodplain where earthworks are located. The poor stratigraphic demarcation of the ridges and well dug channels, with no evidence for agriculture whatsoever, support the idea that some raised fields was strategic for distributing groundwater and rainwater over a large area and thus preserving the productivity of the wetland for fishing and hunting.